Att se bortom seendets gränser - Katz Thor, Rebecka (K&K - Kultur og Klasse, 2022)
This article begins and ends in the question of seeing beyond a mere representation. Drawing on the history of image representations of war, I ask what we can see in images that show very little. The question of seeing stems from Georges Didi-Huberman’s contemplation on the bark from Birkenau and I suggest that his view on seeing could be employed in a wider context. I argue that an alternative view of representations of war and suffering is possible when the motif does not show much since images are far more complex than a superficial deciphering reveals.